Influence of cane molasses inclusion to dairy cow diets during the transition period on rumen epithelial development and a proposed mechanism of rumen epithelial development - Miller, William Frederick (Kansas State University, 2011)
Research regarding rumen epithelial adaptation and potential mechanisms during the transition period of the dairy cow is lacking. The rumen epithelium has a tremendous capacity for the absorption of volatile fatty acids (VFA) produced from microbial fermentation in the rumen. Absorption of VFA from the rumen pool delivers energy substrates to the animal and provides stability to the rumen environment. Increased epithelial surface area from the development and adaptation of rumen papillae facilitates VFA absorption. Manipulation of the diet to alter rumen fermentation can have positive effects upon the rumen papillae development supporting VFA absorption. We hypothesized that enhancing rumen epithelial surface area through dietary alterations could lead to greater VFA absorption and improve rumen stability. Experiments were conducted to determine the effects of diets formulated with cane molasses to stimulate the production of ruminal butyrate and thereby increase rumen epithelial surface area and to investigate a potential mechanism for glucagon-like peptide-2 (GLP-2) to impact epithelial development. Feeding cane molasses in the dry period improved dry matter intake during the close-up period and during lactation. Milk production was increased for cows that were fed cane molasses during the dry period. Ruminal absorption of valerate was greater during the close-up period than the far-off period but was not influenced by the addition of cane molasses. Total VFA concentration measured during the dry period was not affected by the addition of cane molasses to the diet. The presence of glucagon-like peptide receptor (GLP-2R) mRNA was confirmed in bovine tissue obtained from rumen epithelium, omasum, abomasum, duodenum, jejunum, ileum, large intestine, and pancreas. The greatest level of expression of mRNA for GLP-2R was in the small intestine and large intestine. Expression of GLP-2R mRNA during the prepartum period tended to be increased with the addition of cane molasses. Postpartum expression of GLP-2R was not increased by supplementing cane molasses in the dry cow diet. Results from these experiments indicate that dry cow diets formulated to contain cane molasses can positively influence transition cow performance and that the presence of glucagonlike peptide-2 receptor could play a pivotal role in rumen epithelial development.
Keywords: Dairy; Molasses; Rumen; Epithelium; Glucagon Like Peptide; Animal Sciences (0475)